2005
DOI: 10.1111/j.1475-097x.2005.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time perfusion adenosine stress echocardiography versus myocardial perfusion adenosine scintigraphy for the detection of myocardial ischaemia in patients with stable coronary artery disease

Abstract: Background Real-time perfusion (RTP) contrast echocardiography using low

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
4
2
0
Order By: Relevance
“…As judged by SPECT, there were highly significant agreements for both AM and HR in detecting ischemia. The finding that RTP can be used to accurately detect ischemia is in line with previous investigations [ 11 - 15 , 17 , 18 ]. Although there were no significant differences between AM and HR in agreement, there were some differences worth discussing.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As judged by SPECT, there were highly significant agreements for both AM and HR in detecting ischemia. The finding that RTP can be used to accurately detect ischemia is in line with previous investigations [ 11 - 15 , 17 , 18 ]. Although there were no significant differences between AM and HR in agreement, there were some differences worth discussing.…”
Section: Discussionsupporting
confidence: 91%
“…The similarities and differences between AM and HR were approximately similar in the sole perfusion analysis, as compared with the combined perfusion and wall motion analysis. This indicates that agreement with SPECT can be maintained using wall motion analysis in coronary areas with perfusion artifacts, as previously suggested [ 15 ]. This should be viewed in relation to the results of non-interpretable coronary areas; where the high number of non-interpretable coronary areas in the sole perfusion analysis clearly illustrates lower feasibility, compared to the combined perfusion and wall motion analysis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…CAD ϭ coronary artery disease; RCA ϭ right coronary artery; other abbreviations as in Figure 1. These studies reported 76% to 92% concordance with SPECT by territory, which is comparable to the 79% found in our study involving CMR (20,(22)(23)(24). Similarly, studies comparing MCE with coronary angiography have reported 71% to 92% diagnostic accuracy as compared with 82% in our study (20,21,24 -26).…”
Section: Figure 2 More Examples Showing Cmr and Mce Studiessupporting
confidence: 93%
“…Compared with nuclear myocardial perfusion imaging, stress echocardiography has slightly lower sensitivity (80 vs. 82%) and higher specificity (84 vs. 75%) for the diagnosis of coronary artery disease [41]. It also has greater versatility, lower cost, and no radiation exposure.…”
Section: Comparison Of Echocardiography With Other Imaging Modalitiesmentioning
confidence: 98%